Estudo do espalhamento elástico de projetéis exóticos por alvo de massa intermediária - Almeida, Viviane Morcelle de (2007)
Radioactive beams of 8Li and 6He were produced using the double superconducting solenoid system of RIBRAS (Radioactive Ion Beams in Brasil) with a primary beam of 7Li of Elab = 30 MeV, at the São Paulo Pelletron Accelerator. The production reactions were 9Be(7Li, 8Li)8Be and 9Be(7Li, 6He)10B. The angular distributions of the elastic scattering of the 8Li radioactive beam of 26.0 MeV and 6He radioactive beam of 23.0 MeV were measured on 51V target of 1.9 mg/cm2.The elastic scattering angular distributions were analyzed using Optical Model, where the real and imaginary parts are described through a Non-Local Interaction Model called São Paulo Potential . The results were compared with the data present in the literature. The largest cross section, particularly for the halo 6He, shows evidence of the importance of the break up for these medium mass systems. [1]R. Lichtenthaler et al, Eur. Phys. J. A 25,s01,733 (2005); [2]L.C. Chamon et al, Phys. Rev. C66 (2002) 014610.